THE INFLUENCE OF THE CHRONOTYPE ON THE AWAKENING RESPONSE OF CORTISOL IN THE MORNING - Abbruzzese, Elvira A.; Klingmann, Annina; Ehlert, Ulrike (Advances in Social Sciences Research Journal, 2014)
The chronotype describes the behavioral daytime preference. According to an inherent but interindividually strongly varying biological clock, humans try to best adapt to their environment by tuning their internal clock and therefore their sleep-wake cycle to the social clock, which is reflected by work schedules etc. The chronotype seems to be basically associated with the timing and controlling of the circadian rhythms of biological and psychological parameters. In general, morning types show earlier acrophases and maximum values of biological factors compared to evening types. Like most physiological parameters cortisol follows a strong circadian rhythm, with a peak immediately after awakening, the so-called cortisol awakening response (CAR). Since glucocorticoids in general are assumed to play a key role in the timing and synchronization of the internal clock and the regulation of the transcription in the DNA, a well-tuned CAR might be crucial for the synchronization of one’s own organism to the environment. Purpose Since a stable circadian rhythm in general seems to be health-protective, we aimed to determine the association between the chronotype and the CAR in 25 healthy men. Results Our results suggest that evening types show a lower total amount of cortisol, but a significantly prolonged phase of cortisol increase within the first hour after awakening. Conclusion Our data might suggest that an inadequate synchronization between inert chronotype and environment results in an extenuated CAR.